Rancang Bangun Alat Otomatisasi Pengomposan dari Sampah Organik Berbasis Internet of Things - Rahman, Nurfadilah; Purnamasari, Rita; Eliskar, Yulinda (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Organic waste management in Indonesia is currently suboptimal. Approximately 33.7% of waste is not properly managed, and 56% of the total waste consists of organic waste, most of which comes from households. Composting is an effective method for managing organic waste. However, many people are still reluctant to convert organic waste into compost due to the lengthy process, which typically takes 2 to 3 months. This study proposes an IoT-based composting automation system with the goal of accelerating the composting process without the use of additional microorganisms, producing both dry and liquid compost. The system method involves integrating Internet of Things (IoT) technology with sensors: DHT22 for temperature monitoring, soil moisture sensors for measuring soil moisture, MQ-4 sensors for detecting methane gas, pH sensors for measuring soil acidity, and water level sensors for detecting the height of liquid compost. Data collected from these sensors is used to automatically control the organic waste mixing process until all composting specifications are met. The results indicate that this system effectively accelerates the composting process to 24 days for dry compost and 19 days for liquid compost without the need for additional microorganisms, while producing compost of high quality according to the SNI-19-7030-2004 specifications.